Non invasive monitoring in mechanically ventilated pediatric patients. (December 2014) - Al-Subu, Awni M; Rehder, Kyle J; Cheifetz, Ira M; Turner, David A
<x xml:space="preserve">Abstract</x> Cardiopulmonary monitoring is a key component in the evaluation and management of critically ill patients. Clinicians typically rely on a combination of invasive and non-invasive monitoring to assess cardiac output and adequacy of ventilation. Recent technological advances have led to the introduction: of continuous non-invasive monitors that allow for data to be obtained at the bedside of critically ill patients. These advances help to identify hemodynamic changes and allow for interventions before complications occur. In this manuscript, we highlight several important methods of non-invasive cardiopulmonary monitoring, including capnography, transcutaneous monitoring, pulse oximetry, and near infrared spectroscopy.